Controllable growth of conducting polymers shell for constructing high-quality organic/inorganic core/shell nanostructures and their optical-electrochemical properties - Xia, Xinhui (2013)
High-quality metal oxide/conducting polymer (CP) heterostructured nanoarrays are fabricated by controllable electrochemical polymerization of CP shells on preformed metal oxides nanostructures for both electrochromic and electrochemical energy storage applications. Coaxial and branched CP shells can be obtained on different backbones (nanowire, nanorod, and nanoflake) simply by controlling the electrodeposition time. “Solvophobic” and “electrostatic” interactions are proposed to account for the preferential growth of CP along metal oxides to form core/shell heterostructures. The coaxial TiO2/polyaniline core/shell nanorod arrays exhibit remarkable electrochromic performance with rich color changes, fast optical modulation, and superior cycling stability. In addition, the Co3O4/polyaniline core/shell nanowire arrays are evaluated as an anode material of Li ion battery and exhibit enhanced electrochemical property with higher and more stable capacity than the bare Co3O4 nanowires electrode. These unique organic–inorganic heterostructures with synergy pave the way for developing new functional materials with enhanced properties or new applications.